Effectiveness of lidocaine patches for pain treatment after total knee arthroplasty - Sadigursky,David (2017)
BACKGROUND: Effective analgesic therapy in the postoperative period of total knee arthroplasty is essential for good surgical outcomes. The current trend is to use multimodal treatment, in which the use of patches with lidocaine as adjuvant therapy has an increasingly relevant role. OBJECTIVE: To investigate the potential benefits of lidocaine patch association with the basic analgesia regimen for pain relief during the postoperative period of total knee arthroplasty. METHOD: A retrospective cohort study was performed , with a total of 24 patients in each group, who underwent total knee arthroplasty. Pain levels using a visual analogue scale and opioid intake were controlled from the immediate postoperative to the end of a 28-day interval. RESULTS: During the postoperative period, pain was less intense in patients who used lidocaine patches. In these same patients, the doses of opioids needed to control pain were lower in 15 of the 28 days analyzed. The relative frequency of nausea was higher in the group that did not use adjuvant therapy. Patients older than 70 years and females predominated. CONCLUSION: Adjuvant treatment after total knee arthroplasty using lidocaine patches was effective in reducing pain and decreasing the use of opioids in the period analyzed, and represents a good addition to multimodal analgesic therapy.